The psychological impact of COVID-19 pandemic on physicians in Saudi Arabia: A cross-sectional study - Eman Al Sulais; Mahmoud Mosli; Turki AlAmeel (The Saudi Journal of Gastroenterology, 2020)
Background/Aim: COVID-19 pandemic exposed physicians to extraordinary stress and made them vulnerable to various types of psychological illnesses. The aim of this study was to evaluate the impact that the COVID-19 pandemic had on the psychological well-being of physicians. Materials and Methods: We performed a cross-sectional, survey-based study, targeting physicians in Saudi Arabia during the COVID-19 pandemic. The primary outcome was to assess the psychological impact that the pandemic had on physicians by using a questionnaire that was previously designed and used by Reynold's et al. to survey Canadians during the SARS outbreak in 2003. The questionnaire assessed respondents' understanding of the rationale for quarantine, quarantine behaviors (including difficulties and compliance), as well as socio-economic and psychological impacts through answers that are based on a Likert scale. We also assessed the possible risk factors for psychological disorders related to the pandemic. Results: The study included 529 physicians from various regions in Saudi Arabia. The enrolled physicians were practicing different specialties and branches in medicine. We classified them based on their workplace in relation to COVID-19 exposure to: COVID-19 designated center vs. non-COVID-19 designated centers. Furthermore, we subdivided the physicians who work in COVID-19 designated centers to those who work in high-risk areas such as ER, ICU and COVID-19 isolation wards and other areas as low-risk areas. The most common feelings reported by the physicians during the pandemic were: worry (357, 67.5%), isolation (301, 56.9%) and fear (263, 49.7%). According to logistic regression analysis, physicians older than age 60 were less likely to feel isolated (OR = 0.08, 95% CI = 0.01-0.96, P = 0.05), female physicians were more likely to experience fear (OR = 2.96, 95% CI = 1.20 – 7.27, P = 0.02) and worry (OR = 2.87,95% CI = 1.23 – 6.69, P = 0.02), while physicians with a previous exposure to similar traumatic events were less likely to experience fear (OR = 0.24, 0.10 – 0.64, P = 0.004) during the COVID-19 pandemic. Conclusions: The COVID-19 pandemic had a negative psychological effect on physicians in Saudi Arabia. Gender, age, and previous exposure to similar traumatic events were predictive of psychological reactions to the pandemic in this population.